2016
DOI: 10.1186/s12906-016-1315-6
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine sulfate suppresses the expression of matrix metalloproteinase-3 in osteosarcoma cells in vitro

Abstract: BackgroundGlucosamine, a common dietary supplement, has a possible anti-sarcoma effect. However, an understanding of the underlying mechanism of such an effect is limited. For this study we hypothesized that glucosamine suppresses the basal level of matrix metalloproteinase expression in human osteosarcoma cell lines.MethodsWe examined the osteosarcoma cell lines, MG-63 and SaOS-2. Cells were exposed to 0, 10, 50 and 100 μg/ml glucosamine sulfate for 48 h and treatment toxicity was determined through measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Matrix metalloproteinases (MMPs) are enzymes known to degrade the ECM, and 23 types have been reported in humans [46]. Of these enzymes, MMP-1, -2, -3, -8, -9, -13, and -14 have been reported to be involved in promoting the migration and infiltration of osteosarcoma cells [47,48,49,50,51,52,53,54]. The substrate of MMP-1, -8, and -13 is type I collagen, and that of MMP-2, -3, -9, and -13 is type IV collagen, and furthermore, laminin is another substrate of MMP-2, -3, and -14.…”
Section: Aberrant Expression Of Mirna Related To Invasion and Metamentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are enzymes known to degrade the ECM, and 23 types have been reported in humans [46]. Of these enzymes, MMP-1, -2, -3, -8, -9, -13, and -14 have been reported to be involved in promoting the migration and infiltration of osteosarcoma cells [47,48,49,50,51,52,53,54]. The substrate of MMP-1, -8, and -13 is type I collagen, and that of MMP-2, -3, -9, and -13 is type IV collagen, and furthermore, laminin is another substrate of MMP-2, -3, and -14.…”
Section: Aberrant Expression Of Mirna Related To Invasion and Metamentioning
confidence: 99%
“…Therefore, we also confirmed the reliability of our candidate drugs by consulting the relevant literature in PubMed. Glucosamine, which is a common dietary supplement, has immunosuppressive effects on autoimmune diseases [34,35]. Chien et al confirmed Glucosamine could reduce IL2 downstream signaling through downregulating IL2RA [36], while IL2 and IL2RA ( CD25 ) were upregulated in patients with MG, and IL2RA might affect the clinical symptoms of MG [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…Pohlig et al. found a pronounced suppressive effect of glucosamine sulfate particularly on MMP‐3 and ‐9 mRNA and protein levels in OS cell lines in vitro . Hirahata et al.…”
Section: Targeting Mmps: Prospects In Clinical Applicationmentioning
confidence: 98%